A nonmyeloablative chimeric mouse model accurately defines microglia and macrophage contribution in glioma. (17th May 2018) - Yu, K.; Youshani, A. S.; Wilkinson, F. L.; O'Leary, C.; Cook, P.; Laaniste, L.; Liao, A.; Mosses, D.; Waugh, C.; Shorrock, H.; Pathmanaban, O.; Macdonald, A.; et al.
Abstract : Aims: Resident and peripherally derived glioma associated microglia/macrophages (GAMM) play a key role in driving tumour progression, angiogenesis, invasion and attenuating host immune responses. Differentiating these cells' origins is challenging and current preclinical models such as irradiation‐based adoptive transfer, parabiosis and transgenic mice have limitations. We aimed to develop a novel nonmyeloablative transplantation (NMT) mouse model that permits high levels of peripheral chimerism without blood‐brain barrier (BBB) damage or brain infiltration prior to tumour implantation. Methods: NMT dosing was determined in C57BL/6J or Pep3/CD45.1 mice conditioned with concentrations of busulfan ranging from 25 mg/kg to 125 mg/kg. Donor haematopoietic cells labelled with eGFP or CD45.2 were injected via tail vein. Donor chimerism was measured in peripheral blood, bone marrow and spleen using flow cytometry. BBB integrity was assessed with anti‐IgG and anti‐fibrinogen antibodies. Immunocompetent chimerised animals were orthotopically implanted with murine glioma GL‐261 cells. Central and peripheral cell contributions were assessed using immunohistochemistry and flow cytometry. GAMM subpopulation analysis of peripheral cells was performed using Ly6C/MHCII/MerTK/CD64. Results: NMT achieves >80% haematopoietic chimerism by 12 weeks without BBB damage and normal life span. Bone marrow derived cells (BMDC) and peripheral macrophages accounted for approximately 45% of the GAMM population in GL‐261 implanted tumours. Existing markers such as CD45 high/low proved inaccurate to determine central and peripheral populations while Ly6C/MHCII/MerTK/CD64 reliably differentiated GAMM subpopulations in chimerised and unchimerised mice. Conclusion: NMT is a powerful method for dissecting tumour microglia and macrophage subpopulations and can guide further investigation of BMDC subsets in glioma and neuro‐inflammatory diseases.